Adaptive fractional‐order control of power system frequency in the presence of wind turbine. Issue 4 (19th December 2019) - Kazemi, Mohammad Verij; Gholamian, S. Asghar; Sadati, Jalil
Abstract : Inertial and droop control are common methods for improving grid frequency control. Using the first‐order derivative of the frequency in the inertial control loop only investigates the rate of frequency variation, while other useful information is not taken into consideration. Accordingly, in this study, the application of a fractional‐order derivative (between 1 and 2) in the inertial control loop is proposed to have more useful frequency‐based information. To achieve this goal, firstly continued fraction approximations and secondly, the discretization is adopted by using the Tustin Method with Prewarping. Inertia loop and droop loop gain have a significant impact on the operation of the wind turbines and the power system frequency control. Therefore, in this paper, a novel method for the adaptive adjusting of droop and inertia control loops gains in DFIG is proposed. To utilize more frequency error information, fractional‐order adaptive law is proposed to update the loop gains and the inertia control loop. In order to have a robust system, which is permanently stable for every fractional order (FO), is used parameter space method. Simulation results demonstrate the proper performance of the FO‐based adaptive approach to increase the frequency nadir (FN) and decrease the frequency variations.